2013
DOI: 10.4315/0362-028x.jfp-13-004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Sampling Methods for the Microbiological Analysis of Broiler Carcasses after Immersion Chilling

Abstract: Countries have different official programs and implement different sampling methods for the detection of Salmonella on poultry carcasses. In Brazil, a 25-g sample of skin and muscle excision (SME) from the wings, neck, and pericloacal parts is used; in the European Union (EU), a 25-g sample of neck skin (NSE) is used; and, in the United States, the whole carcass is rinsed with 400 ml of diluent (WCR). In the present study, these methods were evaluated to compare Salmonella occurrence and counts of hygiene indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The differences may be accounted for by many factors including high prevalence of Salmonella spp. in live broilers at slaughter, hygienic practices during slaughter at the wet markets [ 10 , 55 ] and sensitivity of the laboratory techniques used in the isolation of the organism [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The differences may be accounted for by many factors including high prevalence of Salmonella spp. in live broilers at slaughter, hygienic practices during slaughter at the wet markets [ 10 , 55 ] and sensitivity of the laboratory techniques used in the isolation of the organism [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the challenges associated with WCE method, particularly the considerably larger incubator space requirement compared with the use of WCR and NS methods, cannot be disregarded thereby making it an impractical method for routine surveillance testing but applicable as a research tool. It has been reported that the types of samples and the methods of enrichment affect their sensitivities to detect Salmonella in chickens [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…H ow ever, W C R takes tim e and space and requires carcasses to be rem oved from the shackle line. N eck or other skin excision with or w ithout underlying m uscle is som etim es used to sam ple broiler carcasses (11,13). Stom aching o f excised skin is considered to be an effective m ethod for rem oval o f firm ly attached bacterial cells (11).…”
mentioning
confidence: 99%